2015
DOI: 10.1007/s00464-015-4282-y
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic hepaticojejunostomy after bile duct injury

Abstract: The benefits of minimally invasive approaches in BDI seem to be feasible and safe, even when this is a complex and catastrophic scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…Similarly, Laukkarinen et al, 2010 [ 69 ], found low rates of anastomotic leakage or stricture in their experimental models when performed Roux-en-Y HJ with a transanastomotic stents, also, Moris et al, 2016 [ 70 ] recorded low stricture rate when performed HJ with stenting for biliary obstruction of different causes. On contrary, the outcome of Roux-en-Y HJ that was performed laparoscopically by Cuendis-Vela´zquez et al, 2016 [ 7 ] was good at maximum 36 months follow-up without using stents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, Laukkarinen et al, 2010 [ 69 ], found low rates of anastomotic leakage or stricture in their experimental models when performed Roux-en-Y HJ with a transanastomotic stents, also, Moris et al, 2016 [ 70 ] recorded low stricture rate when performed HJ with stenting for biliary obstruction of different causes. On contrary, the outcome of Roux-en-Y HJ that was performed laparoscopically by Cuendis-Vela´zquez et al, 2016 [ 7 ] was good at maximum 36 months follow-up without using stents.…”
Section: Discussionmentioning
confidence: 99%
“…The use of trans-anastomotic stents is controversial [ 2 , 7 , 15 , 67 ]. However, some investigators reported the benefit of stents in avoiding recurrent cholangitis [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging data come from the evaluation of minimal invasive approaches to perform HJ, even in severe BDI injuries. In the laparoscopic setting, it was recently showed that laparoscopic approach to BDI repair is feasible and safe with low morbidity rates (bile leak, 17.2%, reintervention, 6.8%) accompanied with the well-established advantages of laparoscopic surgery (low pain, earlier mobilization, and cosmesis) [ 38 ]. In the setting of malignancies, the results are not that satisfactory since the morbidity rate reached 33.3% and mortality was 2.08% in a series of laparoscopic HJ cases for palliative treatment of pancreatic head malignancy [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, evidence on late repair of biliary strictures by laparoscopic hepaticojejunostomy is scarce. Long term follow-up of these patients is not known (63,64). Laparoscopic repair of biliary strictures should only be considered in research protocols in highly specialized centers.…”
Section: D) Can Biliary Injuries Be Repaired Laparoscopically?mentioning
confidence: 99%